On stepwise advancement of fractures and pressure oscillations in saturated porous media. (15th June 2019) - Peruzzo, C.; Simoni, L.; Schrefler, B.A.
Highlights: Importance of an appropriate crack tip advancement/time stepping algorithm. Possible pitfalls with inappropriate algorithms. Crack forerunning as an additional source of stepwise crack tip advancement. Continuum models can indeed capture stepwise crack tip advancement.